Аналіз використання електрошлакових технологій для рециклінгу сталевої стружки - Веретільник, О.В.; Біктагіров, Ф.К. (Physico-technological Institute of Metals and Alloys, 2024)
The article is devoted to the problem of steel shavings processing. It is shown that electroslag melting has high refining capabilities for obtaining high-quality metal from highly contaminated chips. The peculiarities of various methods of electroslag melting of non-compact charge are considered. The prospect of non-briquetted shavings processing by the method of electroslag crucible melting (ESCM) was noted. When melting high-carbon steel, it is possible to use a non-consumable graphite electrode as a current conductor. When processing low- and medium-carbon steels and alloys, it is necessary to use a metal consumable electrode of the same grade of metal as the shavings as a current conductor. Research and experiments on joint melting of shavings and a consumable electrode made of heat-resistant alloys CrNi70WMoTiAlV, CrNi75MoNbTiAl and stainless steel Cr18Ni10Ti in an electric slag crucible furnace with a capacity of 120 kg were carried out. With the amount of shavings fed to the melting, 50-55 % of the total mass of the metal being remelted, and the furnace being fully loaded, the specific electricity consumption was from 0.48 to 0.55 kWh/kg, and the productivity was from 141.4 up to 170.5 kg/h. The content of alloying elements in heat-resistant alloys and stainless steel due to the adjustment of the slag composition and the possibility of doping while melting was within the standard composition for these metals. The high quality of the metal obtained from waste by the ESCM method is confirmed by the data of mechanical tests of the metal plates with a thickness of 65 and 80 mm made of Cr18Ni10Ti steel, which by all indicators exceed the requirements of the technical conditions for similar cast blanks. The performed analysis shows the prospects of using electroslag crucible melting for recycling steel shavings.